Effectiveness and Safety of Contrast Cryolipolysis for Subcutaneous-Fat Reduction - Marília Bueno Savacini; Débora Tazinaffo Bueno; Ana Carolina Souza Molina; Ana Caroline Almeida Lopes; Caroline Nogueira Silva; Renata Gomes Moreira; Stephani Almeida; Renata Michelini Guidi; Estela Sant’Ana; Richard Eloin Liebano (Dermatology Research and Practice)
Cryolipolysis is the noninvasive treatment of localized fat through cold-induced panniculitis. The purpose of the present study was to evaluate the safety and efficacy of contrast cryolipolysis for subcutaneous-fat reduction. Contrast cryolipolysis mixes the principles of conventional cryolipolysis and periods of heating in accordance with the contrast lipocryolysis process. Twenty-one subjects aged 34 ± 9 years were treated with contrast cryolipolysis in the regions of abdomen and flanks through the Polarys® device. Anthropometry, standardized photographs, measurements with a skinfold caliper, and diagnostic ultrasounds were performed at the baseline and during follow-ups at 30, 60, and 90 days after the treatment. The safety assessments included laboratory testing and monitoring of the adverse events. The level of significance for all tests was set at P < 0.05. No significant differences in weight and body mass index were found. The waist measurements at the baseline and 30-day follow-up had significant differences, as did the measurements at the 30-day and 60-day follow-ups. The skinfold and ultrasound measurements were significantly reduced in the treated areas in all the time points compared to the baseline. The laboratory results showed no significant changes from baseline. Temporary adverse effects were resolved spontaneously. This study confirmed that contrast cryolipolysis is safe and effective in reducing the fat layer and improving body contouring.